2001
DOI: 10.1111/j.1348-0421.2001.tb01268.x
|View full text |Cite
|
Sign up to set email alerts
|

A Non‐Surgical Rat Model of Foreign Body‐Associated Urinary Tract Infection with Pseudomonas aeruginosa

Abstract: This study established a rat model of foreign body-associated urinary tract infection. A spiral polyethylene tube (PT) was placed transurethrally into the bladder without surgical manipulation, followed by transurethral inoculation with Pseudomonas aeruginosa. The persistence of P. aeruginosa in the kidneys and bladder was significantly enhanced by placement of the PT, whereas the bacteria were eliminated rapidly from the urinary tract in the animals without the PT. Scanning electron microscopy revealed a thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
38
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 13 publications
4
38
0
2
Order By: Relevance
“…Our findings are in line with previous reports demonstrating that CFU recovered from experimental E. faecalis and Pseudomonas aeruginosa infections are higher in catheterized animals as compared with noncatheterized animals (14,35,37). Indeed, that the ID 90 for E. faecalis and UPEC are greatly reduced in catheter-bearing animals compared with noncatheterized mice highlights the truly vulnerable host state induced by catheter implantation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings are in line with previous reports demonstrating that CFU recovered from experimental E. faecalis and Pseudomonas aeruginosa infections are higher in catheterized animals as compared with noncatheterized animals (14,35,37). Indeed, that the ID 90 for E. faecalis and UPEC are greatly reduced in catheter-bearing animals compared with noncatheterized mice highlights the truly vulnerable host state induced by catheter implantation.…”
Section: Discussionsupporting
confidence: 83%
“…Catheterization induces physical changes in the bladder and provides a structural surface permitting colonization by uropathogens. In animal studies, infected and noninfected catheterized bladders show profound tissue damage, including disruption of the epithelial barrier, as compared with noncatheterized infected rodents (14,35). Our studies have revealed that the initial inflammatory host response to catheterization is sustained for at least 1 week, as evidenced by continuous neutrophil recruitment to the catheterized bladder.…”
Section: Discussionmentioning
confidence: 78%
“…21 The catheter also damages the bladder mucosa by triggering an inflammatory response and by mechanical erosion. 18,22 Once organisms gain access to the catheterized urinary tract, low-level bacteriuria usually progresses to >10 5 colony-forming units/mL within 24 to 48 hours in the absence of antimicrobial therapy. 23 For patients with an indwelling urethral catheter, the daily rate of acquisition of bacteriuria is 3% to 10%.…”
mentioning
confidence: 99%
“…The insertion and presence of indwelling urinary catheters disrupt the normal mechanical and host defenses of the urinary tract, allow extracellular microbes access to the sterile environment of the bladder by ascending through the catheter lumen or from the urethral meatus along the catheter, and provide an additional surface for biofilm formation and the establishment of antibioticrecalcitrant chronic or recurrent infections (2)(3)(4)(5)(6)(7)(8)(9). Even in the absence of microbial colonization, urinary catheterization was shown to be associated with histological and immunological alterations in the bladder, including urothelial damage and exfoliation, bladder wall edema, inflammatory cytokine production, immune cell infiltration, and mucosal lesions of the bladders and kidneys (7,(10)(11)(12)(13) which can lead to bladder cancers (14,15). However, there remains a need to uncover molecular details and the functional role of the catheter-induced host responses during bacterial colonization and catheter-associated UTIs (CAUTIs).…”
mentioning
confidence: 99%